Environmental Sanitation with Diarrhea in the Elderly - Ester Ester; Trimaya Cahya Mulat; A. Suyatni Musrah; Lina Yunita; A. Syamsinar Asmi (Edukasi Ilmiah Indonesia, 2023)
Abnormal bowel movements more than three times a day with concentrations of watery stools with or without blood or mucus due to inflammatory processes in the stomach or intestines. Purpose: Knowing environmental sanitation with the incidence of diarrhea in the elderly. Method: The research design used was an analytic survey using a cross sectional study, the population in this study was the elderly, a sample of 30 respondents. Results: The statistical test shows that the chi square test for clean water supply has a value of ? = 0.045, family latrines ? = 0.045, household waste management ?=0.045, and SPAL ?=0.049. Conclusion: That there is a relationship between clean water supply, use of family latrines, household waste management, and SPAL with the incidence of diarrhea in the elderly. Water is very important for human life. Efforts can be made to improve the provision of clean water, provision of latrines, management of solid waste, management of liquid waste, and efforts to improve environmental sanitation programs.